Gaseous ozone treatment of chickpea grains, part I: Effect on protein, amino acid, fatty acid, mineral content, and microstructure. (30th May 2021) - Nickhil, C.; Mohapatra, Debabandya; Kar, Abhijit; Giri, Saroj Kumar; Tripathi, Manoj Kumar; Sharma, Yogesh
Graphical abstract: Highlights: Protein bands remain unaltered while SH bond decreased and SS increased. Total Amino acid content decreased without affecting the PER and BV with ozonation. Ozonation improved the amount of beneficial fatty acids. Minerals were not affected at the lower dose of ozonation. Modification of intracellular cell wall without affecting the starch structure. Abstract: The effect of gaseous ozone (500–1000 ppm) treatment on the protein, amino acid, and fatty acid profiles, mineral content, and the microstructure of the chickpea grains were evaluated. Though protein content was not altered significantly, SDS PAGE profiling exhibited minor modifications in the protein bands of the treated chickpea. The essential amino acids (EAA) and total amino acids (TAA) slightly decreased, ratio of EAA to TAA increased, while the calculated protein efficiency ratio decreased. Significant decrease in the SH content and non-significant increase in SS content was observed at higher doses of ozone. The overall saturated and unsaturated fatty acids (%) were in the range of 13.05–13.49 and 86.51–87.61, respectively. The minerals were stable and the HCl extractability decreased in the ozonated samples. There was some minor degradation of intracellular cell wall and distribution of starch and protein bodies in the ozonated sample.